Evaluation of Balikpapan City bylaw No. 16/2000 on the Prohibition, Supervision, Control, Circulation and Sale of Alcoholic Beverages in Balikpapan City - Totalia, Sherly Sustantien; Irawan, Bambang; Saipul (Pascasarjana Universitas Mataram, 2025)
The aim of the research is to describe and analyze the factors inhibiting the implementation of Regional Regulation Number 16 of 2000 concerning Prohibition, Supervision, Controlling the Distribution and Sale of Alcoholic Drinks in the City of Balikpapan. This research uses a qualitative approach to describe the problems and research focus. Based on the results of research related to the Evaluation of Balikpapan City Regional Regulation Number 16 of 2000 concerning Prohibition, Supervision, Control, Distribution and Sale of Alcoholic Drinks in Balikpapan City, it can be concluded that the effectiveness of implementation is still hampered by weak law enforcement and illegal practices that are still widespread, the efficiency of implementation requires a more adequate budget allocation and better cooperation between related parties, the scope of the regulations is still being debated by various parties, especially regarding the fundamental value of law and the relevance of the Regional Regulations, the fairness of the implementation of the Regional Regulations needs to be improved to avoid injustice towards business actors outside the area of star hotels in accordance with Rawls' principles of justice, responsiveness of government and society are important to ensure compliance with regulations, and the accuracy of regional regulations requires revision and evaluation through strong public participation to achieve the desired goals. Overall, collaboration between the government, police, business actors and the community is key in facing challenges and increasing the effectiveness of regulations regarding alcoholic drinks in Balikpapan City.